PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA MATERI STATISTIKA KELAS VI MI MAMBAUL ULUM KELBUNG GALIS BANGKALAN - Makrifah, Nurul; Romlah, Siti (JEMI, 2023)
The problems that exist in improving student learning outcomes in Mathematics subjects in class VI MI Mambaul Ulum Kelbung are students' passive response and students' interest in learning in Mathematics subjects is low and students have the perception that Mathematics is a difficult subject to learn so that in When learning takes place, students pay less attention to explanations from educators, causing low student learning outcomes. Therefore, the formulation of the problem in this research is "How is the Talking Stick Type Cooperative Learning Model Implemented in Improving Student Learning Outcomes in Mathematics Subjects, Statistics Material in Class VI MI Mambaul Ulum, Smangkaan Hamlet, Kelbung Village, Galis District, Bangkalan Regency, Academic Year 2021/ 2022. Data analysis techniques use averages. Based on the learning outcomes of students after using the talking stick type cooperative learning model, there has been an increase. This can be seen from the increase in students' classical completeness in cycle I by 58.33% and in cycle II by 83.33%, an increase of 25%. From the results of the analysis above, it can be understood that the use of the talking stick type cooperative learning model can improve student learning outcomes and can be used as an alternative for Mathematics learning at MI Mambaul Ulum Kelbung.